The Incidence of Subsidies to Residential Public Services in Argentina: The Subsidy System in 2014 and Some Alternatives - Lakner, Christoph (2016)
More than a decade of energy and transport subsidies have weakened Argentina’s fiscal capacity. Following the 2001 crisis, public services tariffs were frozen in an attempt to offset the negative effects on households’ real purchasing power. However, these subsidies steadily increased over the years, particularly since 2006, becoming a significant fiscal burden.2 Though subsidies can be a tool to protect the poor, in Argentina they led to distortions and a large share have been absorbed by upper classes and non-residential consumers. In 2015, electricity bills reflected less than 10% of production costs (Bidegaray, 2015), and lower tariffs have led to an increased demand of public services. Not only have energy and transport subsidies distorted both demand and supply, they have also not been efficiently targeted to the poor; instead, they have been distributed across all income groups, with the non-poor receiving the largest shares (Castro and Barafani, 2015; Lombardi et al., 2014; Marchionni et al., 2008; Navajas, 2015; Puig and Salinardi, 2015). For a recent discussion of the distortionary aspects of subsidies in Argentina, see Coppola et al. (2016). This report starts by analyzing the incidence of the 2014 system of residential federal subsidies to residential public services (defined as electricity, gas, water and transport) building on the work by Puig and Salinardi (2015).3 Figure 1 is a summary of the main results that will be explained in more detail in Section II. The left panel of Figure 1 shows the share of each subsidy going to the various quintiles of the income distribution. The public subsidies are in decreasing order of the share received by the poorest quintile which we have used here to describe targeting. It is clear that the subsidies to trains, piped gas and airlines benefit the richer segments disproportionally more. Electricity appears relatively neutral which still means that it could be targeted better. Programa Hogar is included in our incidence analysis, even if it was not introduced until 2015, since it will be used for the baseline of the simulation.